Pengaruh Pemanfaatan Fasilitas Belajar Terhadap Mutu Layanan Akademik Program Studi Di Sekolah Pascasarjana Universitas Pendidikan Indonesia - Khairul Azan (Jurnal Penjaminan Mutu, 2018)
One of the efforts to improve the quality of higher education is to provide excellent service on the academic needs of each student as a user (customer) of service college. Several factor which effect the quality of academic services include adequate learning facilities in terms of services that fit the student needs. This research is motivated by the gap between empirical phenomena and t he prevailing theory, where student often do not feel satisfied with the quality of academic services provided, such as facilities are not in accordance with the expectations of students as cutomers. This study aims to describe and analyze the effect of learning facilities utilization towards quality of academic services for study program at the School of Postgraduate Studies Indonesia University of Education. The methode used in this study is a survey methode with a quantitative approach. The data collection technique used is a questionnaire. The sampled-subject are students from 36 existing courses at the School of Postgraduate Studies Indonesia University of Education amounting to 352 student. The result show that the general picture of the quality of academic services for study program at School of Postgraduate Studies Indonesia University of Education are in the category. As for the use of learning facilities in the fairly well category. Utilization of the facilities have a significant influence on the quality of academic services for study program.